Características bucodentales en 15 pacientes con insuficiencia motríz de origen cerebral -IMOC- del Instituto Julio H. Calonje (IDEAL) Cali 2002 - Lores Trujillo, Liliana; Rodríguez Prada, Katherine; Vázquez Erazo, Rosamary; Hernández, Jesús Alberto (Revista Estomatología, 2002)
This study determined the bucodental characteristics in 12 boys and 3 girls having muscle paralysis of brain origin (MPBO) aged 7-15 years old. All patients, had complete dental history, dental impressions and cast models. Eight patients had permanent dentition, most subjects had a straight facial profile, overbite 4-9mm, anterior openbite and europrosopic facial pattern. It is suggested that MPBO, could induce short and wide faces (euriprosopic), anterior openbite and dear disturbances on the length and wide of the dental arches. A preventive treatment of this anomalies way include early diagnosis, and facial/dental therapy. A controlled study should determine if MPBO is associated with an euriprosopic facial pattern and anterior dental openbite.